Bulletin of Industrial Statistics for Arab Countries - Eighth issue - Nations Unies (United Nations, 2015)
This publication provides detailed industrial data of Arab countries for policy-makers, analysts and researchers. It includes time series of data and indicators for the period 2006- 2012. The Bulletin is divided into two parts. Part I includes summary tables on the overall industrial trends like the levels of output expressed as the per capita value added at constant prices, labor productivity expressed as the share of value added at constant prices per employee, and the size of the contribution made by industry to gross domestic product (GDP) at producers’ prices. Part II contains tables of industrial statistics for each Arab country – the number of establishments, the number of employees, wages and salaries, output, value added and the industrial production index numbers.